Mechanisms of endothelial cell protection by curcumin in hypercholesterolemia - Sri Agus Sudjarwo, Koerniasari Eraiko Sudjarwo, Giftania Wardani Sudjarwo, Koerniasari (Journal of Applied Pharmaceutical Science)
Mechanism of curcumin for protection of endothelial cell was studied in cholesterolfed rabbits. Thirty rabbits were randomly divided into five groups. The negative control group was fed a standard diet, the positive control group was fed the same diet with 2 % cholesterol , the curcumin group was fed the same diet with 2 % cholesterol and curcumin 100 mg/Kg BW/day, 200 mg/Kg BW/day or 400 mg/Kg BW/day. The cholesterol-rich diet significantly increased Malondialdehyde (MDA) in the aortic blood vessels, as reflected by Thiobarbituric Acid-Reactive Substances (TBARS), inhibited endothelium-dependent vascular relaxations to acetylcholine and decrease cyclic GMP were compared with vessels from normal rabbits (negative control). In cholesterol-fed rabbits, curcumin treatment decreased MDA in plasma production, improved endothelium - dependent relaxations to acetylcholine and increase cyclic GMP production. These results suggest that dietary treatment of rabbits with curcumin may prevent superoxide anion (O2-) induced inactivation of endothelium-dependent relaxing factor(EDRF), improve the endothelium-dependent relaxation to acetylcholine in the aortic blood vessels and increase cyclic GMP content in aortic of cholesterol-fed rabbits.
Keywords: Curcumin, Malondialdehyde, EDRF, cyclic GMP.